KARAKTERISTIK PENDERITA AIDS DAN INFEKSI OPURTUNISTIK DI RUMAH SAKIT UMUM PUSAT (RSUP) H. ADAM MALIK MEDAN TAHUN 2012 - Andy Yusri Rangkuti; Sori Muda Sarumpaet; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
AIDS is a set of symptomps due to the decreased of immune system caused by HIV. One of the causes of the high mortality of AIDS patients is Opportunistic Infection (OI). Ministry of Health Republic of Indonesia reported the highest OI is Oral Candidiasis (80,8%), TB Paru (40,1%), Cytomegalovirus (28,8%), Toxoplasma Encephalitis (17,3%), Pneumocystis Carinii Pneumonia (13,4%), Herpes Simplex (9,6%), Mycobacterium Avium Complex (4,0%), Criptosporodiosis (2,0%), and Pulmo Hystoplasmosis (2,0%). To determine the  characteristics of AIDS patients and OI, conducted a research at RSUP H. Adam Malik Medan with case series design. Population and sample was 223 patients in 2012 and recorded in hospital medical records. Univariate data were analyzed descriptively while bivariate data were analyzed using Chi-square test with 95% CI. Based on sosiodemographic, the highest population is in the age group of 29-35 years old (41,7%), male (74,0%), Batak (78,5%), graduated high school/equivalent (62,8%), work (83,0%), married (70,4%), and came from Medan area (52,0%). The highest OI type is Oral Candidiasis (35,3%), heterosexual transmission (67,3%), CD4 count < 200 cells/mL (80,7%), and underweight (72,2%). There is a significant differentiation of proportion between the work based on the transmissions infection (p=0,024). There is no significant differentiation of proportion between age based on the transmissions infection, sex based on the transmissions infection, married based on the transmissions infection, the BMI based on CD4 count, and CD4 count based on clinical stadium. Statistical test can not be performed for tribe based on place. It is hoped the high risk group of HIV/AIDS in order to prevent with “ABC”, to stop at all or does not use needles, to the parties to concern in implementing effective screening, to people living in HIV to improve nutrition and take ARV obediently, to officers of  medical records to complete the record of adherence and BMI and to coordinate the data in the hospital medical records with the data source from Pusyansus VCT in order not to make misunderstanding. Keywords : AIDS, Oppurtunistic Infection, Characteristics of Patients, RSUP H. Adam Malik Medan 2012